2022
DOI: 10.9734/ejmp/2022/v33i130443
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants Used for Management of Asthma in FCT, Abuja and Its Environs

Abstract: Aim: Asthma is a condition that affects the airways in human lungs. It causes its (lungs) inflammation and hyper-responsiveness. Conventional therapies used in its management are expensive and have been found to come with undesirable side effects. The use of herbal remedies in treating the disease is widespread especially in local communities with little or no access to primary health care. This indigenous knowledge on the cure of asthma is gradually being lost among the populace. This study is aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The decoction is considered an effective method for extracting the active ingredients of medicinal plants (Gao et al 2022), and it can also lessen or eliminate the negative effects of some recipes (Chaachouay et al 2019, Iwaka et al 2022. Moreover, it is cheap and also easy (Adigwe et al 2022) to prepare by mixing the plant with water, tea, milk, and so.…”
Section: Discussionmentioning
confidence: 99%
“…The decoction is considered an effective method for extracting the active ingredients of medicinal plants (Gao et al 2022), and it can also lessen or eliminate the negative effects of some recipes (Chaachouay et al 2019, Iwaka et al 2022. Moreover, it is cheap and also easy (Adigwe et al 2022) to prepare by mixing the plant with water, tea, milk, and so.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the recipes administered by the TMPs are in liquid form which is typical of herbal concoctions and recipes [9][10][11]. As part of their practice, it was revealed that the majority (between 87% to 89%) of the TMPs kept patient and recipe records and also referred patients to hospitals when they think the illness is best handled by conventional medicine.…”
Section: Discussionmentioning
confidence: 99%